Development Of Cost-Efeffective Demonstration Hydraulic Physical Model Of Debris Flow - Yasser, Karam Shamdeen (Universiti Sains Malaysia, 2022)
Identified cost benefit of materials used for debris flow model and construct and test efficiency of demonstration debris flow model. Debris flows are geological phenomena in which masses of water-filled soil and fragmented rock accelerate to the slopes of mountains, infiltrate the course of rivers, enter objects in their tracks, and form sediments Dense mud in the valley floors. Fiberglass, ferrocement and plywood were used to build our model. The study tested the effectiveness of the model by calculating Q=Av. The study did a survey of several stores, factories, and companies to acquire the right price to determine the cost benefit of materials used for debris flow model and to construct and test efficiency of the demonstration debris flow model. The model achieved a good and effective price. The final model cost in terms of basic material prices was Rm 10,701. The purpose of this research was to determine the cost of the materials used to construct the model and to evaluate its performance. This will make it easier for researchers and students to profit from the study in the future.